Maternal burn-out: an exploratory study. (27th May 2018) - Séjourné, N.; Sanchez-Rodriguez, R.; Leboullenger, A.; Callahan, S.
Abstract: Introduction: Maternal burn-out is a psychological, emotional and physiological condition resulting from the accumulation of various stressors characterised by a moderate but also a chronic and repetitive dimension. Little research has focused on this syndrome. Objective : The current study aims to assess maternal burn-out rate and to identify factors associated with this state of exhaustion. Method: 263 French mothers aged between 20 and 49 years answered five scales quantifying maternal burn-out, perceived social support, parental stress, depression and anxiety symptoms and history of postnatal depression. Results: About 20% of mothers were affected by maternal burn-out. The main factors related to maternal burn-out were having a child perceived as difficult, history of postnatal depression, anxiety, satisfaction of a balance between professional and personal life and parental stress. Conclusion: This research shows the need for further work on maternal burn-out to better understand and prevent this syndrome.